Complexes of Fe(III) and Ga(III) Derived from the Cyclic 6‐ and 7‐Membered Hydroxamic Acids Found in Mixed Siderophores. Issue 13 (9th March 2023) - Jewula, Pawel; Grandmougin, Mickaël; Choppin, Mélanie; Tivelli, Anna Maria Chiara; Amati, Agnese; Rousselin, Yoann; Karmazin, Lydia; Chambron, Jean‐Claude; Meyer, Michel
Abstract: Six‐ and seven‐membered cyclic hydroxamic acids are found as terminal binding units in different families of siderophores, including exochelins and mycobactins. The simplest models of these preorganized chelating ligands were known, but their coordination chemistry with Fe 3+, the target metal ion of siderophores, had never been reported. Four complexes were synthesized and studied: two Fe 3+ complexes, one with the six‐membered ring hydroxamate PIPO − and one with the seven‐membered ring hydroxamate AZEPO −, and the two corresponding Ga 3+ complexes. X‐ray diffraction studies showed that the interligand repulsion energies were better minimized in the case of the AZEPO − complexes whatever the metal cation considered, and that the Fe−O bond distances were shorter in [Fe(AZEPO)3 ] by comparison with [Fe(PIPO)3 ]. Abstract : The structures of the six‐coordinate Fe(III) and Ga(III) complexes of the cyclic 6‐ and 7‐membered hydroxamic acids PIPOH and AZEPOH found in several mixed‐ligand siderophores are intermediate between the octahedron (OC) and the trigonal prism (TPR). The coordination geometries of [M(AZEPO)]3 are very close to OC, whereas the coordination geometry of the [Fe(PIPO)3 ] complex is half‐way between OC and TPR.